(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2018)
A six month’s experiment was carried out in earthen ponds to evaluate the effect of micro and macro nutrients on the growth performance of Prawn (Macrobrachium rosenbergii), Rohu (Labeo rohita) and Mola (Amblypharyngodon mola) in a polyculture system during July to December 2017. The trial was conducted into two different treatments and one control each with three replications. In treatment-1, macronutrients enrich fertilizers like urea, TSP and molasses-yeast mixture were applied at the rate of 2.45, 2.45, and 3.09 (g m-2 week-1), whereas in treatment-2 micronutrients composition mixer applied at the rate of 4.50 g m-2 week-1 while no micro and macronutrients were applied in control. The mean value of all water quality parameters showed no significant differences among control and two treatments when One-way ANOVA was performed except hardness. The average final mean individual weights of prawn, rohu and mola in control, treatment-1 and treatment-2 were 22.10, 24.35, and 24.70 g; 141.10, 190.60 and 182.20 g; 3.36, 3.67 and 3.73 g, respectively. The survival rates of various species namely prawn, rohu and mola in control, treatment-1 and treatment-2 were 73.33, 89.58 and 86.25%; 78.00, 74.00 and 74.00%; 10.67, 15.33 and 15.33%, respectively. There was no significant difference in the survival rates of prawn, rohu and mola among control and treatments. Production after six months of culture was 351.8, 461.5 and 445.3 kg ha-1 in control, treatment-1 and treatment-2, respectively which were significantly different at 5% level of significance. Int. J. Agril. Res. Innov. & Tech. 8 (2): 47-53, December, 2018